Model Sumur Resapan dan Drainase Untuk Penanggulangan Banjir Dengan Memanfaatkan Material Lokal - Yuliyanti Kadir; Indriati Martha Patuti; Frice L. Desei (Universitas Muhammadiyah Surabaya, 2017)
Flooding is a disaster that often occurs in the rainy season. The damage caused by this failure is not only material damage such as damage to houses, public facilities, and destruction of agricultural land, but also create disease outbreaks around the disaster site. One solution to reduce rainwater runoff needs to be made easy and practical recharge well model by utilizing local materials. The purpose of this research is the modeling of absorbing wells and drainage for prevention and control of flood hazard to achieve a healthy, safe, and comfortable. The research location is Lauwonu Village, Tilango District, Gorontalo Regency. Construction materials for modeling are local materials located around the site. The recharge wells are sized (2x1x1) m3 and (2x1,5x1) m3. If every household has a recharge well with a minimum volume of 2 m3, it will reduce rainfall runoff so that that flood disaster can be avoided.